MED resulting from recessively inherited mutations in the gene encoding calcium‐activated nucleotidase CANT1. Issue 9 (25th July 2017) - Balasubramanian, Karthika; Li, Bing; Krakow, Deborah; Nevarez, Lisette; Ho, Patric J.; Ainsworth, Julia A.; Nickerson, Deborah A.; Bamshad, Michael J.; Immken, LaDonna; Lachman, Ralph S.; Cohn, Daniel H.
Abstract : Multiple Epiphyseal Dysplasia (MED) is a relatively mild skeletal dysplasia characterized by mild short stature, joint pain, and early‐onset osteoarthropathy. Dominantly inherited mutations in COMP, MATN3, COL9A1, COL9A2, and COL9A3, and recessively inherited mutations in SLC26A2, account for the molecular basis of disease in about 80–85% of the cases. In two families with recurrent MED of an unknown molecular basis, we used exome sequencing and candidate gene analysis to identify homozygosity for recessively inherited missense mutations in CANT1, which encodes calcium‐activated nucleotidase 1. The MED phenotype is thus allelic to the more severe Desbuquois dysplasia phenotype and the results identify CANT1 as a second locus for recessively inherited MED.